Scoping Ethical AI in Working Life: Lessons for the Nordic Model - Larsson, Christoffer; Launberg, Anna; Lindell, Eva (Nordic Journal of Working Life Studies, 2025)
The Nordic working life is characterized by high union density, flat organizations, and trust. In this context, ethical artificial intelligence (AI) implementation requires dialogue and collective decision-making between employers and employees. This scoping review displays argumentations in scientific literature about AI implementation in working life through five ethical frameworks: utilitarianism, rights-based justice, distributive justice, ethics of care, and virtue ethics. Results show that rights-based ethics and ethics of care are the most prominent framings, while utilitarian and distributive justice arguments rather support tensions between efficiency and fairness. This displays how AI’s promise of efficiency exists in tension with fundamental working life values such as transparency, fairness, and collective wellbeing. As the Nordic model is under pressure, in parallel with the structural shifts that follow AI implementation, this study highlights how ethical leadership will be more important to ensure that AI implementation strengthens the collective values that have historically distinguished Nordic working life.